1995
DOI: 10.1074/jbc.270.49.29286
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Nuclear Translocation of Mitogen-activated Protein Kinases by Polyomavirus Middle-T or Serum Depend on Phosphatidylinositol 3-Kinase

Abstract: Several cellular signal transduction pathways activated by middle-T in polyomavirus-transformed cells are required for viral oncogenicity. Here we focus on the role of phosphatidylinositol 3-kinase (PI 3-kinase) and Ras and address the question how these signaling molecules cooperate during cell cycle activation. Ras activation is mediated through association with SHC.GRB2.SOS and leads to increased activity of several members of the mitogen-activated protein (MAP) kinase family, while activation of PI 3-kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
(57 reference statements)
2
47
1
3
Order By: Relevance
“…This result points to an essential role for PI3K in the AP-1 activation by MT. Urich et al (1995) have shown that MT activates and induces MAPK nuclear translocation, this e ect being dependent upon MT binding to Shc and PI3K. In our experiments, MT binding to Shc and PI3K also seems to be essential for complete MAPK activation (data not shown).…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…This result points to an essential role for PI3K in the AP-1 activation by MT. Urich et al (1995) have shown that MT activates and induces MAPK nuclear translocation, this e ect being dependent upon MT binding to Shc and PI3K. In our experiments, MT binding to Shc and PI3K also seems to be essential for complete MAPK activation (data not shown).…”
Section: Discussionsupporting
confidence: 44%
“…However, high AP-1 activity is observed in the 250phe mutant (that does not bind Shc) even though the Erk1 activity displayed by this cell line is low. Interestingly, the 250phe mutant is only 50% less e ective than WTMT to induce the uPA promoter (Urich et al, 1995). As discussed by the authors (Urich et al, 1995) low levels of MAPK in the nucleus, undetectable by immunostaining, could be present in the 250phe cell line.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations